Forestry and ecological features of distribution and improvement of biotic stability of pine forests in the conditions of Lviv region - Hryhoriy Krynytskyy; Mykola Korol; Vasyl Lavnyy; Valentyna Kovaleva; Volodymyr Kramarets; Olga Krynytska; Volodymyr Mahuran (Наукові праці Лісівничої академії наук України, 2023)
In the context of climate change and growing anthropogenic pressure, identified were the features of the distribution and silvicultural indicators of the functioning of pine stands in Lviv region, taking into account various types of forest site conditions. Measures have been developed on silvicultural and ecological principles to increase biotic stability and to preserve Scots pine stands.